2020
DOI: 10.1371/journal.pone.0237439
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stage at presentation for incarcerated patients at a single urban tertiary care center

Abstract: Patients who are incarcerated are a vulnerable patient population and may suffer from less access to routine cancer screenings compared to their non-incarcerated counterparts. Therefore, a thorough evaluation of potential differences in cancer diagnosis staging is needed. We sought to examine whether there are differences in cancer stage at initial diagnosis between non-incarcerated and incarcerated patients by pursuing a retrospective chart review from 2010-2017 for all patients who were newly diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Almost two-thirds of patients diagnosed with cancer while incarcerated and more than half of those diagnosed following release were found to have regional spread or metastasized cancer, including for screenable cancers such as colorectal cancer. These data support the previously reported trend of late-stage cancer diagnosis in the incarcerated population [13]. Past research has indicated that incarcerated individuals are less likely to receive age-appropriate screening and this disparity warrants immediate health system intervention [27].…”
Section: Plos Onesupporting
confidence: 85%
See 2 more Smart Citations
“…Almost two-thirds of patients diagnosed with cancer while incarcerated and more than half of those diagnosed following release were found to have regional spread or metastasized cancer, including for screenable cancers such as colorectal cancer. These data support the previously reported trend of late-stage cancer diagnosis in the incarcerated population [13]. Past research has indicated that incarcerated individuals are less likely to receive age-appropriate screening and this disparity warrants immediate health system intervention [27].…”
Section: Plos Onesupporting
confidence: 85%
“…While prior studies have identified the association between incarceration and cancer survival time [13], our study illuminates the immediate post release period as a particularly highrisk time period. People diagnosed shortly following release from correctional settings are more likely to die earlier from cancer compared with counterparts diagnosed during incarceration, likely reflecting the significant barriers following release for obtaining timely cancer care.…”
Section: Plos Onementioning
confidence: 69%
See 1 more Smart Citation
“…There is also a high positivity rate of infections such as human papillomavirus, HIV, and hepatitis C that increase the risk of cancer development including lung, liver, and anorectal cancers. 3,10,11 In general, the US population is aging and the incarcerated population is no exception. With the gradual rise in mean age of incarcerated individuals throughout the last several years, 12 the correctional system has steadily seen an increase in prevalence of chronic medical conditions including cancer, a condition now recognized as the leading cause of mortality in the incarcerated population older than 45 years (Figure 1).…”
Section: The Burden Of Cancer In the Us Correctional Systemmentioning
confidence: 99%
“…According to the 2016 US Bureau of Justice Statistics report, incarcerated individuals 55 years or older roughly tripled from 2001 to 2016 (4% to 12%, respectively), an increase of more than 200%. [10][11][12] Furthermore, according to the American Civil Liberties Union, by 2030, more than one-third of individuals in prison in the US will be older than 55 years. 13 The 2020 US Bureau of Justice Statistic report noted that individuals older than 55 years had the highest mortality rate of all incarcerated individuals (more than 3 times as high as any other age group).…”
Section: The Burden Of Cancer In the Us Correctional Systemmentioning
confidence: 99%